2015
DOI: 10.1371/journal.pone.0121060
|View full text |Cite|
|
Sign up to set email alerts
|

Antisecretory, Gastroprotective, Antioxidant and Anti-Helicobcter Pylori Activity of Zerumbone from Zingiber Zerumbet (L.) Smith

Abstract: Background Zingiber zerumbet Smith is a perennial herb, broadly distributed in many tropical areas. In Malaysia, it’s locally known among the Malay people as “lempoyang” and its rhizomes, particularly, is widely used in traditional medicine for the treatment of peptic ulcer disease beyond other gastric disorders.Aim of the studyThe aim of the current study is to evaluate the gastroprotective effect of zerumbone, the main bioactive compound of Zingiber zerumbet rhizome, against ethanol-induced gastric ulcer mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
75
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 63 publications
9
75
0
1
Order By: Relevance
“…Several medicinal plants have been used to protect the stomach from a number of ulcerative agents. One type of medicinal plant is C. barometz leaves, which are used to stop bleeding [13]. In this study, the results of acute toxicity experiment revealed no signs of toxicity or mortality in vivo and no variations in kidney and liver on biochemical investigation.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Several medicinal plants have been used to protect the stomach from a number of ulcerative agents. One type of medicinal plant is C. barometz leaves, which are used to stop bleeding [13]. In this study, the results of acute toxicity experiment revealed no signs of toxicity or mortality in vivo and no variations in kidney and liver on biochemical investigation.…”
Section: Discussionmentioning
confidence: 58%
“…Cibotium is a tropical native medicinal plant in the Malaysian Peninsula and parts of China. It is an anti-inflammatory plant and is used in contradiction of rheumatic and menstruation problems, as well as herniated discs and hyperosteogeny [13, 14]. There are many phenolic compounds in Cibotium that are potent antioxidants and strong chelators.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, oxidative stress may cause induction and the aggravation of gastric ulcer. 20 Catalase and SOD are essential to the body in order to discharge the harmful ROS from the cellular environment. 21 The present study showed that mean SOD and catalase levels were significantly increased in extract treated-500 group-III, extract treated-1000 group-IV and standard drug treated group-V as compared to that decreased in ulcer control group-II rats.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sidahmed et al showed antibacterial activity on S. choleraesuis, however no antifungal activity was observed, Moreover, it exerted an antiproliferative effect on HeLa cells [5]. Similarly, Sidahmed et al evaluated the gastroprotective effect of zerumbone and the results depict that zerumbone promotes ulcer protection along with antioxidant activity and maintenance of mucus integrity [6]. It also has been shown to have anti-inflammatory and antioxidant properties [7].…”
Section: Introductionmentioning
confidence: 99%